Plant structural traits and their role in anti-herbivore defence - Hanley, Mick; Lamont, Byron; Fairbanks, Meredith; Rafferty, Christine (Elsevier, 2007)
We consider the role that key structural traits, such as spinescence, pubescence, sclerophylly and raphides, play in protecting plants from herbivore attack. Despite the likelihood that many of these morphological characteristics may have evolved as responses to other environmental stimuli, we show that each provides an important defence against herbivore attack in both terrestrial and aquatic ecosystems. We conclude that leaf-mass–area is a robust index of sclerophylly as a surrogate for more rigorous mechanical properties used in herbivory studies. We also examine herbivore counter-adaptations to plant structural defence and illustrate how herbivore attack can induce the deployment of intensified defensive measures. Although there have been few studies detailing how plant defences vary with age, we show that allocation to structural defences is related to plant ontogeny. Age-related changes in the deployment of structural defences plus a paucity of appropriate studies are two reasons why relationships with other plant fitness characteristics may be obscured, although we describe studies where trade-offs between structural defence and plant growth, reproduction, and chemical defences have been demonstrated. We also show how resource availability influences the expression of structural defences and demonstrate how poorly our understanding of plant structural defence fits into contemporary plant defence theory. Finally, we suggest how a better understanding of plant structural defence, particularly within the context of plant defence syndromes, would not only improve our understanding of plant defence theory, but enable us to predict how plant morphological responses to climate change might influence interactions at the individual (plant growth trade-offs), species (competition), and ecosystem (pollination and herbivory) levels.